Fostering Students’ Reflective Thinking Skill Using Problem Solving-based Student Worksheets in Mathematics Learning - Agustan Syamsuddin; Hasdah Haking; Idawati Idawati (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2021)
Students need to be equipped reflective thinking skill in solving mathematics problem. To achieve it, teaching material such as problem solving-based worksheet in mathematics learning is needed. Therefore, this study aims to increase student’s reflective thinking skill by using problem solving-based worksheet. This research involved 35 fifth grade elementary school students in Pangkep, Makassar. The research design used was pre-experiment with a pretest-posttest control group design. Data were collected through tests of reflective thinking skill and analyzed using descriptive and inferential statistics. The results showed that the students' pretest mean score is 54.30. While the student’s posttest mean score is 81.30. The result of the calculation of the gain index was 0.59 which is in the medium category. This indicates that there was an increase in the score of students' reflective thinking skill. The t-test results obtained by the t-value of 11.58 > t-table of 2.03 with a significant value of 0.000 <0.05. This explains that there was a difference in the mean score before and after using problem solving-based worksheet in learning mathematics. This study concluded that using problem solving-based worksheets can foster students' reflective thinking skill.